UiTM Selangor innovation carnival 2023 / Dr. Aisyah Hasyila Jahidin - Jahidin, Aisyah Hasyila (Faculty of Pharmacy, 2023)
On 14th and 15th January 2023, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) participated in the UiTM Selangor Branch (UCS) Innovation Carnival 2023 which was organised by UCS in collaboration with the Ministry of Science, Technology and Innovation (MOSTI). The innovation carnival which took place at the Diamond Hall of UCS Puncak Alam Campus was officiated by Chief Secretary of MOSTI, YBhg. Datuk Ts. Dr. Haji Aminuddin Hassim. Also present were UiTM Vice Chancellor, YBhg. Profesor Datuk Ts. Dr. Hajah Roziah Mohd Janor, UiTM officials, UCS Management, lecturers and staff of UCS, sponsors, industry partners, media and visitors.